2018
DOI: 10.1002/2211-5463.12345
|View full text |Cite
|
Sign up to set email alerts
|

miR‐373 regulates inflammatory cytokine‐mediated chondrocyte proliferation in osteoarthritis by targeting the P2X7 receptor

Abstract: Inflammatory cytokines commonly initiate extreme changes in the synovium and cartilage microenvironment of osteoarthritis ( OA ) patients, which subsequently cause cellular dysfunction, especially in chondrocytes. It has been reported that induction of the purinergic P2X7 receptor (P2X7R) can regulate the expression of a variety of inflammatory factors, including interleukin ( IL )‐6 and ‐8, leading to OA pathogenesis. However, knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…IL-6 transsignaling will skew the differentiation of monocytes to macrophages through the upregulation of the macrophage colony-stimulating factor (M-CSF) receptor [45]. A significant increase of IL-6 and IL-8 has been observed in patients with osteoarthritis [46][47][48][49][50][51]. For instance, Favero et al determined the inflammatory molecules produced from coculture of meniscus tissue and synovial membrane from patients with early-stage (n = 5) and end-stage (n = 5) osteoarthritis [47].…”
Section: The Role Of Cytokines In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 transsignaling will skew the differentiation of monocytes to macrophages through the upregulation of the macrophage colony-stimulating factor (M-CSF) receptor [45]. A significant increase of IL-6 and IL-8 has been observed in patients with osteoarthritis [46][47][48][49][50][51]. For instance, Favero et al determined the inflammatory molecules produced from coculture of meniscus tissue and synovial membrane from patients with early-stage (n = 5) and end-stage (n = 5) osteoarthritis [47].…”
Section: The Role Of Cytokines In Osteoarthritismentioning
confidence: 99%
“…NF-κB is the downstream signaling pathway of TAK1; thus, upregulated TAK1 causes increased activation of NF-κB in osteoarthritis [104]. Zhang et al demonstrated that miR-373 decreased in osteoarthritis and it targeted P2X7 receptor (P2X7R) [49]. P2X7R expression was enhanced in osteoarthritis; this led to increased chondrocyte proliferation and release of inflammatory factors such as IL-6 and IL-8.…”
Section: The Role Of Mirna In Osteoarthritismentioning
confidence: 99%
“…8 As an example, miR-373 expression was reported to be downregulated in OA patient chondrocytes, while its overexpression promoted chondrocyte proliferation by inhibiting the expression of P2X7 receptor and inflammatory factors. 2 Interleukin (IL)-1b also promoted the occurrence of OA and degradation of the ECM through regulating the mitogen-activated protein kinase/nuclear factor-jB pathway by inhibiting miR-27a-3p. 9 Recently, miR-146a-5p was shown to play an important regulatory role in a variety of tumors, including gastric cancer, lung cancer, and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage-protective effects are mediated by miR-140 via targeting ADAMTS5, MMP13 and HDAC4 driving expression of COL2A1 and ACAN ( Tuddenham et al, 2006 ; Miyaki et al, 2009 ; Si et al, 2020 ). OA progression is accompanied by decreased miR-337 expression and loss of miR-337 shifts the equilibrium from anabolism of cartilage tissue to bone formation, ( Zhang et al, 2018b ). Studies frequently find more upregulated than downregulated miRNAs in OA ( Ntoumou et al, 2017 ; Coutinho, de Almeida et al, 2019 ).…”
Section: Ev-associated Mirnas As Potential Diagnostic Biomarkers For mentioning
confidence: 99%